A food-poisoning incident caused by Clostridium botulinum toxin A in Japan. - Otofuji, T. (Cambridge University Press, 1987)
Food poisoning caused by Clostridium botulinum toxin A occurred in Japan. Eleven (31%) of 36 patients from 14 different areas died of botulism. Most of the patients had eaten commercial fried lotus-rhizome solid mustard without heating. The food, which implicated one of the special local products used for gifts in Kumamoto, was found to have been produced by a manufacturer in Kumamoto prefecture. In Fukuoka prefecture, two of three patients died on days 4 and 8 after eating the food; they had typical symptoms of botulism. A total of 42 packages of the food bought as gifts was collected from different districts in Fukuoka prefecture for examination for both organism and toxin. Thirteen of these (31%) were contaminated with the organism, and in 11 (26%) a small amount of toxin A had been produced.